2013
DOI: 10.1093/icvts/ivt021
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted azygos lobectomy for adenocarcinoma arising in an azygos lobe

Abstract: The azygos lobe is a well-known and well-described anatomical variation of the right lung. Primary lung cancer arising from an azygos lobe, however, is exceedingly rare. Only a handful of cases have been previously reported in the literature. We report the first case with operative demonstration of a primary adenocarcinoma arising from an azygos lobe, which was treated with robot-assisted azygos lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 3 publications
1
24
0
1
Order By: Relevance
“…It has no serious consequences by itself, and there is no need for special treatment; however, accompanying conditions may warrant attention. Bronchial carcinoma, pneumothorax, bullous changes, and vascular abnormalities have been reported to accompany AL [1, 5–7]. Various approaches have been successfully employed for those pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has no serious consequences by itself, and there is no need for special treatment; however, accompanying conditions may warrant attention. Bronchial carcinoma, pneumothorax, bullous changes, and vascular abnormalities have been reported to accompany AL [1, 5–7]. Various approaches have been successfully employed for those pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies on the subject is limited; however, it is worth noting the report by Fukuhara et al [5], in which a patient with non-small-cell lung cancer originating from the azygos lobe was operated on using a robot-assisted technique.…”
Section: Discussionmentioning
confidence: 99%
“…The rst report of a right upperlobectomy by video-assisted thoracic surgery (VATS) in a patientwith an azygos lobe was published by Arai et al [10]. Some tumors may originatedirectly from the azygos lobe reported in several research [9,19,20]. In Fukuharaet al [20]research, they rstly reported the case with operativedemonstration of a primary adenocarcinoma arising from an azygoslobe, which was treated with robot-assisted azygos lobectomy.…”
Section: Treatmentmentioning
confidence: 99%
“…Azygos lobe related tumors are defined in the literatures. Superior sulcus tumor arising in an azygos lobe [14], azygos lobe small cell carcinoma [15], and adenocarcinoma arising in an azygos lobe [16]. Superior sulcus tumors usually arise in the apex of the lung and may invade the brachial plexus, the subclavian vessels, the second and third ribs, the stellate ganglion and adjacent vertebral bodies [14].…”
mentioning
confidence: 99%
“…However, neither the surgical/oncological implication of having a tumour confined to an azygos lobe, nor the reasons for rarity of cancer development in this lobe is known, despite its being a common anatomical variance. One theory hypothesizes that this rarity of cancer development results from decreased ventilation of the azygos lobe [16], While this is a controversial assumption, the ventilation of an azygos lobe may be relatively limited due to constriction by the azygos vein, possibly resulting in less oxygen delivery and particle deposition of carcinogens thereby restricting carcinogenesis within this lobe despite its apparent segmental or subsegmental bronchovascular supply [16].…”
mentioning
confidence: 99%